2010
DOI: 10.1111/j.1440-1843.2010.01770.x
|View full text |Cite
|
Sign up to set email alerts
|

Creatine supplementation for patients with COPD receiving pulmonary rehabilitation: A systematic review and meta‐analysis

Abstract: Creatine supplementation does not improve exercise capacity, muscle strength or HR-QoL in patients with COPD receiving PR. However, important limitations were identified in the quality of the available evidence, suggesting that further research is required in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 49 publications
(133 reference statements)
1
13
0
1
Order By: Relevance
“…33 Although Cr displays several beneficial therapeutic effects, 2,[12][13][14][15][16]20,21,34 other studies have also found that Cr supplementation does not have a beneficial effect on the respiratory system during respiratory diseases. 15,[35][36][37] This study, however, indicates that Cr supplementation presents beneficial effects after lung I/R injury, including improvements in lung mechanics and inflammation. These contradictory findings in the context of the respiratory diseases are probably related to the pathophysiologic differences between the respiratory diseases under study (i.e., chronic obstructive pulmonary diseases vs acute lung injury).…”
Section: Discussionmentioning
confidence: 51%
“…33 Although Cr displays several beneficial therapeutic effects, 2,[12][13][14][15][16]20,21,34 other studies have also found that Cr supplementation does not have a beneficial effect on the respiratory system during respiratory diseases. 15,[35][36][37] This study, however, indicates that Cr supplementation presents beneficial effects after lung I/R injury, including improvements in lung mechanics and inflammation. These contradictory findings in the context of the respiratory diseases are probably related to the pathophysiologic differences between the respiratory diseases under study (i.e., chronic obstructive pulmonary diseases vs acute lung injury).…”
Section: Discussionmentioning
confidence: 51%
“…Small pilot investigations have suggested potential benefits of whey protein and carnitine, but had insufficient statistical power for wider conclusions to be drawn. Three trials have tested the effect of creatine supplementation during exercise training in COPD with no consistent positive effect, as confirmed by a subsequent systematic review and meta-analysis [105]. In a group of overall non-wasted COPD patients, protein and carbohydrate supplementation after resistance exercise did not augment functional or molecular exercise responses [106].…”
Section: Nutrition As Ergogenic Aidmentioning
confidence: 99%
“…In view of this, a number of RCTs of creatine supplementation combined with respiratory rehabilitation have been conducted in COPD patients [58,59,60]. Meta-analyses of these RCTs have, however, failed to show any add-on effect of creatine supplementation in improving the muscle strength of the upper and lower extremities, exercise tolerance (shuttle walk test and 6MWD) or HRQoL (SGRQ score) in COPD patients undergoing respiratory rehabilitation [61]. …”
Section: Creatine Intakementioning
confidence: 99%